A framework for interactive end-user web automation - Eliwa, Essam (2013)
This research investigates the feasibility and usefulness of a Web-based model for end-user Web automation. The aim is to empower end users to automate their Web interactions. Web automation is defined here as the study of theoretical and practical techniques for applying an end-user programming model to enable the automation of Web tasks, activities, or interactions. To date, few tools address the issue of Web automation; moreover, their functionality and usage are limited. A novel model is presented, which combines end-user programming techniques and the software tools philosophy with the vision of the “Web as a platform.” The model provided a Web-based environment that enables the rapid creation of efficient and useful Web-oriented automation tools. It consists of a command line for the Web, a shell scripting language, and a repository of Web commands. A framework called Web2Sh (Web 2.0 Shell) has been implemented, which includes the design and implementation of scripting language (WSh) enabling end users to create and customise Web commands. A number of Web2Sh-core Web commands were implemented. There are two techniques for extending the system: developers can implement new core Web commands, and the use of WSh by end users to connect, customise, and parameterise Web commands to create new commands. The feasibility and the usefulness of the proposed model have been demonstrated by implementing several automation scripts using Web2Sh, and by a case study based experiment that was carried out by volunteered participants. The implemented Web2Sh framework provided a novel and realistic environment for creating, customising, and running Web-oriented automation tools.